Handbook of computer aided geometric design - Farin, Gerald E.; Hoschek, Josef; Kim, Myung-Soo. (Amsterdam ; Boston, Mass. : Elsevier, 2002)
This book provides a comprehensive coverage of the fields Geometric Modeling, Computer-Aided Design, and Scientific Visualization, or Computer-Aided Geometric Design. Leading international experts have contributed, thus creating a one-of-a-kind collection of authoritative articles. There are chapters outlining basic theory in tutorial style, as well as application-oriented articles. Aspects which are covered include: Historical outline Curve and surface methods Scientific Visualization Implicit methods Reverse engineering. This book is meant to be a reference text for researchers in the field as well as an introduction to graduate students wishing to get some exposure to this subject.
A History of Curves and Surfaces in CAGD / Gerald Farin -- Geometric Fundamentals / Wolfgang Boehm, Hartmut Prautzsch -- Geometries for CAGD / Helmut Pottmann, Stefan Leopoldseder -- Bβezier Techniques / Dianne Hansford -- Rational Techniques / Hans J. Wolters -- Spline Basics / Carl de Boor -- Curve and Surface Constructions / Dianne Hansford, Gerald Farin -- Geometric Continuity / Jθorg Peters -- Splines on Surfaces / Marian Neamtu -- Box Splines / Hartmut Prautzsch, Wolfgang Boehm -- Finite Element Approximation with Splines / Klaus Hθollig -- Subdivision Surfaces / Malcolm Sabin -- Interrogation of Subdivision Surfaces / Malcolm Sabin -- Multiresolution Techniques / Leif P. Kobbelt -- Algebraic Methods for Computer Aided Geometric Design / Thomas W. Sederberg, Jianmin Zheng -- Scattered Data Interpolation: Radial Basis and Other Methods / Suresh K. Lodha, Richard Franke -- Pythagorean-Hodograph Curves / Rida T. Farouki -- Voronoi Diagrams / Kokichi Sugihara -- The Medial Axis Transform / Hyeong In Choi, Chang Yong Han -- Solid Modeling / Vadim Shapiro -- Parametric Modeling / Christoph M. Hoffmann, Robert Joan-Arinyo -- Sculptured Surface NC Machining / Byoung K. Choi, Bo H. Kim, Robert B. Jerard -- Cyclides / Wendelin Degen -- Geometry Processing / Thomas A. Grandine -- Intersection Problems -- Reverse Engineering / Tamas Varady, Ralph Martin -- Vector and Tensor Field Visualization / Gerik Scheuermann, Hans Hagen -- Splines over Triangulations / Frank Zeilfelder, Hans-Peter Seidel -- Kinematics and Animation / Bert Jθuttler, Michael G. Wagner -- Direct Rendering of Freeform Surfaces / Gershon Elber -- Modeling and Processing with Quadric Surfaces / Wenping Wang.
Includes bibliographical references and index.
Keywords: Computer graphics; Computer-aided design; CAD; Computergraphics; Electronic books